Impact of ultrasound treatment on molecular structures of casein - Wang, Jinshui; Yin, Yanli; Jia, Feng (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
Casein was modified by ultrasound treatment (160W, 400 W)and the structural characteristics of casein (control), USC-1 (160W of ultrasound treated casein) and USC-2 (400W of ultrasound treated casein) were investigated. Ultrasound treatment resulted in increase in the numbers of protein bands of casein in region of low molecular weight according to SDS-PAGE pattern. The relative percentage of the proteins with molecular mass (MM) of over 30 kD in USC-1 and USC-2 significantly decreased compared with control sample. Coupled with this is the relative percentage of the proteins with MM of region 20 kD-30 kD for the ultrasonic-treated caseins increased. Contents of Î±-helix, Î²-sheet and random coil of casein for USC-1 and USC-2 decreased compared with control. While, Î²-turn content for USC-1 and USC-2 increased. Ratio of Î±-helix to Î²-sheet in USC-1 and USC-2 significantly decreased (from 0.70 to 0.47 and 0.46). Ultrasound treatment had a strong crushing action of surface of the casein micelle and resulted in its structural disruption. Particle size distribution range of casein was approximately 0.5-70 Î¼m, Particle size of USC-1 and USC-2 was less than 30Î¼m. D (50), D (4, 3) as well as D (3, 2) for USC-1 and USC-2 reduced compared with the control. The ratio of D (4, 3) to D (3, 2) also decreased with increase of ultrasonic intensity. This study demonstrated that ultrasound treatment could be an effective method for modification of casein structure. This modification is the basis on improvement in functional properties.